AN OUTLOOK OF FEMINISM MOVEMENT IN THE SELECT NOVELS OF ANITA DESAI AND SHASHI DESHPANDE - P. Sakthivel; N. K. Vivekanandhan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Male is scripted as the head of the family, the guide, the provider, the protector and the moral supporter followed from the ancestry to the present days. The woman is taking decision to handle the responsibility being independently when man is started to lose their own duties. Twenty-first centuries shows the major difference of Indian women. There is no threat of doormats or a damsel in distress is erased in patriarchal norms. Based on this insight, the article discusses about the renowned authors who have achieved worldwide recognition by their outstanding contribution to world literature in the last hundred and fifty-years by the Indian novel Anita Desai’s and Shashi Deshpande’s. On their ideology, the term ‘feminism’ refers global and revolutionary ideology. The aim of socio-cultural of feminism perspective shows the liberation of women from male domination in the patriarchal society shows importance in the modern and postmodern literature. The desire of feminist, women to become self-assertion and self-affirmation through their voice of their writing highlight her position in different aspects. These incidents make them to write with inspirational ideologies, social, political or moral, economic. The authors Anita Desai’s and Shashi Deshpande’s critics the class, gender political and psychosexual conflicts is reduce oppression, suppression in the hands of men related women.